IMPLEMENTASI YURISPRUDENSI MAHKAMAH AGUNG REPUBLIK INDONESIA TERHADAP KEWAJIBAN PENGELOLA PARKIR MENGGANTI RUGI KEHILANGAN KENDARAAN BERMOTOR - RAHMAN, MULIA (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACT This research entitled "Implementation of the Supreme Court of Indonesia's Jurisprudence Against Car Parking Obligers to Loss Loss of Motor Vehicles", the purpose and objective to describe and analyze the management of parking is related to Law Number 8 Year 1999 on Consumer Protection, Business Actors,  and  the  implementation  of the  Supreme  Court's  Jurisprudence  to  the Parking Manager's liability to compensate for loss of motor vehicle. Based on the results of research on legislation, court decisions, and other relevant and relevant sources  that   the   implementation  of  Supreme   Court   jurisprudence  on  the obligations of the parking manager has not been fully implemented. There is still a parking manager who includes a standard clause that reads "any loss or damage is not the responsibility of the parking manager", in this case there is an exoneration clause containing conditions limiting or even removing entirely the responsibility that should be charged to the producer or in this case the manager parking, which is not in accordance with Article 18 Paragraph (1) of the Consumer Protection Act. As a result, there are still cases of disputes in court between the consumer as the owner of the vehicle and the manufacturer as the parking manager that occurs due to loss of motor vehicles in the official parking area.